DISFUNGSIONAL PERAN KARANG TARUNA DALAM PELESTARIAN KEARIFAN LOKAL DI KAMPUNG CIREUNDEU - Ramadhan, Ainun (Universitas Pendidikan Indonesia, 2016)
The Youth Organization of 10 Citizens Associations (RW) that has duty at Cirendeu Village on Leuwi Gajah Administered Dictrict in Cimahi District is an organization that does not do its role well. Hopefulness, according to the Social Ministry Regulation number 77/HUK/2010 the Basic Guidance of Youth Organization on chapter VII concerning the work program article 9 has said â€œEvery Youth Organization has responsibility to determine its work program based on the mechanism, potential, source, ability and local needs of the Youth Organization.â€ In fact, the Youth Organization of 10 Citizens Associations does not touch the local wisdom potential which existence at Cirendeu Village at all. So, the functions of this organization are not felt by Cirendeu Village people. The purpose of conducting this research was to know the performance of Youth Organization at Cirendeu Village recently. Beside that, the researcher wanted to fix this organization on its function and its role based on the people wish. The people of Cirendeu Village wanted to feel the evidence of Youth Organization performance that was profitable for Cirendeu Vilaage. This research used descriptive method with qualitatif approach. To be able to answered the furmolations of the problem, the researher conducted collecting data from interviewee by interview technique, observation and documentation. The datas had been collected, processed, and then analized so that it could be drawing a conclusion. The result of the research showed that there were some the role of dysfunctional Youth Organization such as there was no balancing work program among to custom people. The function of this organization as communicator among the youth was not happened. On the body of this organization itself was not clear because it did not have an organization attribute which should be had by Youth Organization.